The effects of interactive electronic picture books on young children’s oral expression skills - Shao, Yun-Long; Shih, Yi-Huang (International Journal of Education and Practice, 2024)
The application of interactive electronic picture books can strengthen young children’s reading comprehension skills. Interactive electronic picture books that involve interaction with sensors, with the interaction integrated into the story, should be developed to enhance children’s reading experience and improve their oral expression skills. Interactive electronic picture books that involved children manipulating stuffed animals containing sensors that provided feedback were developed for this study. Visual, auditory, and tactile stimuli can be used to create an interactive feedback system. Data was collected through semi-structured interviews with teachers, who gave their opinions regarding the curriculum of their preschool. The results indicate that the intuitiveness of the system helped improve the children’s reading experience, strengthened their motivation to read, and improved their cognitive abilities. In addition, interactive electronic picture books were found to improve the children’s oral expression skills.